Are Mexican Business Cycles Asymmetrical? - Santos, Andre (Washington, D.C. : International Monetary Fund, 2002)
We use the regime-switching econometric models in Hamilton (1989) and Filardo (1994) to study business cycles in Mexico. In particular, we characterize the ups and downs of economic activity in Mexico. As a proxy for economic activity, we use the Mexican quarterly industrial production index from the second quarter of 1972 to the third quarter of 1999. We allow the transition probabilities driving changes in economic activity to be a function of fiscal, financial, and external sector indicators. Our results show that recessions in Mexico are deeper and shorter than expansions.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet